Assessment of knowledge, attitude, and practice of menstrual hygiene amongst school students in rural India - Ravindranath, Wamika; Ravindranath, Venkatesh; Chopade, Rahul R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Lack of information access, traditions, socio-cultural taboos, and hence social embarrassment regarding menstrual hygiene has led to women's health deterioration which led to the development of an embarrassing attitude among women toward practicing menstrual hygiene in rural settings. The information gathered on this issue can be utilized by various NGOs and policymakers to make necessary changes. This study was undertaken to assess the knowledge and attitude about menstruation among school teachers, boys, and girls, including the menstrual hygiene practices of the school girls. Methods: A cross-sectional study was conducted at two schools in Sawarde village, Ratnagiri, India, among 450 boys, 361 girls, and 20 teachers from 7th to 12th grade. Analysis of knowledge, attitude, and practice was done using descriptive analysis. Results: 100% of teachers, 72.02% of female students had good knowledge, while only 32.44% of male students had good knowledge. It was found that 100% of teachers, 28.81% of female students, and only 2.89% of male students had positive attitudes about menstruation. It was found that 90.86% of female students used sanitary pads, 36.29% changed their pads three times or more a day, 52.08% used paper to wrap and dispose of pads, 87.26% disposed it into dustbins, 93.63% cleaned genitalia during menses. Conclusions: IEC and behaviour change communication are needed to spread awareness and empower females regarding menstruation and menstrual hygiene. This program should include girls, their families, peers, and the community.